Financement agricole par l’échange grains / intrants : l’impact de la NPR à Sapezal–MT entre 2004 et 2009 - Argemiro Luís Brum; Charles Luan Marquezin; Wylmor Constantino Tives Dalfovo; Cláudia Regina Heck (Confins)
The CRP (Certificate of rural product) appears as an instrument regulated by the Federal Government in which the producer anticipates its revenues from production in return for having the delivery to private companies for a stipulated amount of its production of soybeans, and this system has gained strength through the spiral of inflation and Brazil’s fiscal crisis of the 1980s, which restricted credit. We sought in this article by addressing the companies of the City of Sapezal-MT describe the costs of purchasing inputs through two distinct mechanisms, the first being the mechanism of the spot purchase with input prices obtained in actual, and the Secondly, the mechanism to run through the CPR, in which prices were analyzed under the exchange system and package of inputs. As a result it has to be the main variable responsible for the success of CPR is the change in commodity prices during the period of the contract and its maturity. Another important result is the fact that most farmers searching for CPR in Sapezal MT are medium-sized producers and on the lenders, large corporations occupy a high percentage of participation in the issuance of such rural negotiations.